Strategi Pendidik Melalui Aktivitas Kegemaran dalam Meningkatkan Bakat Minat Siswa di SD Mutiara Bunda 1 Sidoarjo - Ilham Ubaidillah; Muhammad Yusron Maulana El-Yunusi (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2022)
This study aimed to identify and analyze educators' strategies to improve students' talents and interests through the implementation of favorite activities at Mutiara Bunda 1 Sidoarjo Elementary School. Education plays an important role in developing the potential of each individual, especially students in the stage of growth and development. Increasing students' talents and interests is considered an important aspect of developing individual potential, especially at the basic education level. Students often face challenges in discovering and developing their interest in a formal learning environment. Therefore, it is important for educators to create an atmosphere that allows students to explore their interests through fun activities. The research method used is a qualitative approach, involving direct observation and interviews with teachers and students to determine their interests in various favorite activities that are integrated into the learning process. The results of the research on the indicators of students' increased interest in talent and educators' strategies through favorite activities show that strategies involving favorite activities, such as arts, sports, and skills activities, can significantly increase students' learning motivation and talent exploration. Teachers act as facilitators who support students in expressing their interests as well as directing favorite activities into a means to develop students' cognitive, emotional, and social abilities. In addition, students' involvement in activities that match their interests has a positive impact on academic achievement and self-confidence. This study concluded that the implementation of activity-based strategies is an effective approach for enhancing students' talents and interests. It is hoped that the findings from this study can be used as a guideline for educators to design learning programs that are more appropriate and responsive to students' needs and potential.